IDENTIFICATION OF RESISTANT SOURCES IN GLASS HOUSE AND FIELD EVALUATION OF SOYBEAN GENOTYPES TO ANTHRACNOSE CAUSED BY COLLETOTRICHUM TRUNCATUM (SCHW.) ANDRUS AND MOORE - B. T. NAGARAJ; SHAMARAO JAHAGIRDAR; G. T. BASAVARAJA (The Bioscan, 2014)
Among the nineteen soybean genotypes screened by artificial inoculation with Colletotrichum truncatum, four genotypes viz., DSb 12, DSb 20, DSb 23-5 and Kalitur were found highly resistant with a disease grade of one. The eight genotypes viz., DSb1, DSb 19, DSb 21, JS 95-60, JS 97-52, TGx 1835, EC 241780 and NRC 7 showed moderately resistant reaction with disease grade of 3. The two varieties Himso 1563 and JS 335 showed highly susceptible reaction with disease severity of 9 grades. In field screening of thirteen genotypes, DSb 12 and DSb 20 were found highly resistant to the disease with a grade of one. The five genotypes viz., DSb 1, DSb 19, DSb 21, JS 95-60 and JS 97-52 are fallen under the category of moderately resistant with a disease grade of 3. The genotype JS 335 was highly susceptible to anthracnose with a maximum disease grade of nine.